Khirbat Yajuz, Jordanien - Eger, Christoph (e-Forschungsberichte des DAI, 2023)
One focus of the project „Studies on regional burial customs in Late Antiquity. The necropolis of the 4th–8th cent. AD in the provincia Arabia“ is the necropolis of Khirbat Yajuz in the northern outskirts of the city of Amman. The site has a significant importance as it provides an extraordinary insight into the typical grave furniture and personal adornment of a small town population of the Late Roman and Byzantine period. A systematic study and documentation of the findings has been essential to create a database for further analyses of the burial customs and the material culture.